Innovative method to simulate the self-heating behavior of saturate fractions of a crude oil in a range of low-temperature oxidation. (1st May 2021) - Yang, Lingfeng; Sheng, James J.
Highlights: Developed a kinetic model for fast vapor-phase oxidation of hydrocarbons. Developed a method to simulate the vaporization of hydrocarbons. Provided means to transfer ARC experimental data to field-scale modeling data. Abstract: The air injection process (AIP) has been widely applied to enhance crude-oil recovery. In the last decades, the limited understandings of the oxidation mechanisms complicate the prediction of the performance of AIP. The vapor-phase reaction of hydrocarbons during the low-temperature oxidation (LTO) period in AIP has been mentioned in the literature, but it has not been comprehensively studied because of the limitation of the experimental methods. This study reports a comprehensive CMG-STARS model for simulating the LTO behaviors of saturates by considering both the liquid- and vapor-phase oxidations. A pseudo reaction is introduced in this model to adjust the vaporization rate of the pseudo components. Through adjusting the activation energy, the rate constant, and the enthalpy of the introduced pseudo reaction, the temperature data obtained from the accelerated rate calorimetry (ARC) experiment of the saturates during LTO were well matched by this new model. This study avails a method of transferring ARC experimental data for the design and forecast of AIP projects, and it can greatly increase the understandings of the LTO mechanisms of the saturates of crude oil.